PENGARUH PENGALAMAN KERJA, KOMPETENSI DAN DISIPLIN KERJA TERHADAP PRESTASI KERJA PEGAWAI PADA KANTOR CAMAT AIR HANGAT KABUPATEN KERINCI - Poni Yanita; Dona Elvia Desi (Jurnal Pendidikan Dasar dan Sosial Humaniora, 2022)
The title of this research is the effect of work experience, competence and work discipline on the work performance of employees at the sub-district office of Air Warm, Kerinci Regency. The problem studied in this study is the employee's work performance as seen from the indicators of work experience, competence and work discipline. This study uses a quantitative approach and uses primary data through the distribution of questionnaires to the employees of the Kerinci Air Warmer District Office. The population in this study were 30 respondents with a sampling technique using saturated sampling with Likert scale measurements. The data is processed through the SPSS version 20.0 program with technical multiple linear regression analysis. The results showed that work experience, competence and discipline had a positive and significant effect on employee work performance at the Kerinci District Head Office. From the results of the t test proves that partially the variables of experience, competence and discipline have a significant effect on work performance. Then the results of the F test prove that work experience, competence and discipline simultaneously have a significant effect on work performance at the Kerinci District Head Office with the F-count value greater than the F-table. Based on the results of this analysis, it can be concluded that work experience, competence and work discipline have a significant influence either partially or simultaneously on the work performance of the employees of the Air Warm District Office of Kerinci Regency.